Probing the effects of polymers on the early stages of calcium carbonate formation by stoichiometric co-titration. Issue 17 (23rd March 2022) - Schodder, Philipp I.; Gindele, Maxim B.; Ott, Andreas; Rückel, Markus; Ettl, Roland; Boyko, Volodymyr; Kellermeier, Matthias
Abstract : A modified titration assay with potentiometric and turbidimetric detection was developed to monitor calcium carbonate formation from solution in real time, which delivers new insights into the effects of polymeric additives during crystallisation. Abstract : Potentiometric titrations are a powerful tool to study the early stages of the precipitation of minerals such as calcium carbonate and were used among others for the discovery and characterisation of key precursors like prenucleation clusters. Here we present a modified procedure for conducting such titration experiments, in which the reactants ( i.e. calcium and (bi)carbonate ions) are added simultaneously in stoichiometric amounts, while both the amount of free calcium and the optical transmission of the solution are monitored online. Complementarily, the species occurring at distinct stages of the crystallisation process were studied using cryogenic transmission electron microscopy. This novel routine was applied to investigate CaCO3 nucleation in the absence and presence of polymeric additives with different chemical functionalities. The obtained results provide new insights into the critical steps underlying nucleation and subsequent ripening, such as the role of liquid mineral-rich phases and their transformation into solid particles. The studied polymers proved to interfere at multiple stages along the complex mineralisation pathway of calcium carbonate, with both the degree and mode of interaction depending on the chosen polymer chemistry. In this way, the methodology developed in this work allows the mechanisms of antiscalants – or crystallisation modifiers in general – to be elucidated at an advanced level of detail.